Monitoring of false lumen thrombosis in type B aortic dissection by impedance cardiography – A multiphysics simulation study. (16th December 2022) - Badeli, Vahid; Jafarinia, Alireza; Melito, Gian Marco; Müller, Thomas Stephan; Reinbacher‐Köstinger, Alice; Hochrainer, Thomas; Brenn, Günter; Ellermann, Katrin; Biro, Oszkar; Kaltenbacher, Manfred
Abstract: Aortic dissection is caused by a tear on the aortic wall that allows blood to flow through the wall layers. Usually, this tear involves the intimal and partly the medial layer of the aortic wall. As a result, a new false lumen develops besides the original aorta, denoted then as the true lumen. The local hemodynamic conditions such as flow disturbances, recirculations and low wall shear stress may cause thrombus formation and growth in the false lumen. Since the false lumen status is a significant predictor for late‐dissection‐related deaths, it is of great importance in the medical management of patients with aortic dissection. The hemodynamic changes in the aorta also alter the electrical conductivity of blood. Since the blood is much more conductive than other tissues in the body, such changes can be identified with non‐invasive methods such as impedance cardiography. Therefore, in this study, the capability of impedance cardiography in monitoring thrombosis in the false lumen is studied by multiphysics simulations to assist clinicians in the medical management of patients under treatment. To tackle this problem, a 3D computational fluid dynamics simulation has been set up to model thrombosis in the false lumen and its impact on the blood flow‐induced conductivity changes. The electrical conductivity changes of blood have been assigned as material properties of the blood‐filled aorta in a 3D finite element electric simulation model to investigate the impact of conductivity changes on the measured impedance from the body's surface. The results show remarkable changes in the electrical conductivity distribution in the measurement region due to thrombosis in the false lumen, which significantly impacts the morphology of the impedance cardiogram. Thus, frequent monitoring of impedance cardiography signals may allow tracking the thrombus formation and growth in the false lumen. Abstract : In this work, a combined Computational Fluid Dynamics (CFD) and Finite Element (FE) electric simulation are used to model the false lumen thrombosis in type aortic dissection and its impact on the thoracic impedance measurements by impedance cardiography (ICG). Furthermore, we use a novel approach to model the anisotropic blood conductivity from the blood flow field quantities. We show that such multiphysics simulations are essential to understanding the sources of bioimpedance changes, which in practice are hard to interpret.